Room- and high-temperature torsional shear strength of solid oxide fuel/electrolysis cell sealing material. Issue 2 (1st February 2019) - Fakouri Hasanabadi, M.; Kokabi, A.H.; Faghihi-Sani, M.A.; Groß-Barsnick, S.M.; Malzbender, J.
Abstract: The structural integrity of the sealant material is critical for the reliability of solid oxide fuel/electrolysis stacks. In the current study, a torsion test is implemented to evaluate and compare its shear strength with a partially crystallized glass sealant at room- and operation relevant high-temperatures. Hourglass-shaped specimens with different configurations of hollow- and full-halves are utilized for testing. The fracture surfaces are visualized via optical microscopy and complementary scanning electron microscopy. In addition, cyclic loading is used to investigate potential subcritical crack growth effects in the sealants. Both, the specimens with a hollow-half as well as the ones with two full-halve steel plates yield almost the same nominal shear strengths. The shear fracture stresses decrease with rising temperature, while the fracture mode changes from brittle at room temperature and 600 °C to ductile at 800 °C. The cyclic loading condition indicates subcritical crack growth in the sealant at 600 °C and creep associated damage at 800 °C.